2015
DOI: 10.1107/s1600576715020002
|View full text |Cite
|
Sign up to set email alerts
|

Atomic disorder of Li0.5Ni0.5O thin films caused by Li doping: estimation from X-ray Debye–Waller factors

Abstract: Cubic type room-temperature (RT) epitaxial Li 0.5 Ni 0.5 O and NiO thin films with [111] orientation grown on ultra-smooth sapphire (0001) substrates were examined using synchrotron-based thin-film X-ray diffraction. The 111 and 222 rocking curves including six respective equivalent reflections of the Li 0.5 Ni 0.5 O and NiO thin films were recorded. The RT B 1 factor, which appears in the Debye-Waller factor, of a cubic Li 0.5 Ni 0.5 O thin film was estimated to be 1.8 (4) Å 2 from its 111 and 222 reflection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…It is difficult to visualize the transformation of the lattice structures of these films with increasing Mg content. The calculated atomic order parameter of Mg 0.52 Ni 0.48 O (0.61) is smaller than that of Li 0.5 Ni 0.5 O (0.66) [28], which demonstrates the increased effect of the Mg 2+ ions when compared with that of the Li + on the atomic-scale disorder. This may imply that the preferred occupation of some of the cationic sites when the Mg content is high enough is sufficient to form an ordered solid solution similar to that of Li x Ni 1−x O with x > 0.…”
Section: B Debye Temperaturementioning
confidence: 76%
See 2 more Smart Citations
“…It is difficult to visualize the transformation of the lattice structures of these films with increasing Mg content. The calculated atomic order parameter of Mg 0.52 Ni 0.48 O (0.61) is smaller than that of Li 0.5 Ni 0.5 O (0.66) [28], which demonstrates the increased effect of the Mg 2+ ions when compared with that of the Li + on the atomic-scale disorder. This may imply that the preferred occupation of some of the cationic sites when the Mg content is high enough is sufficient to form an ordered solid solution similar to that of Li x Ni 1−x O with x > 0.…”
Section: B Debye Temperaturementioning
confidence: 76%
“…The above discussion shows that the doped Mg plays an important role in the lattice distortion of the Mg x Ni 1−x O films. To describe the resulting atomic disorder quantitatively, we attempted to evaluate the Debye temperature ( M ) and the Debye-Waller factor (D w i ) of these Mg x Ni 1−x O films from the x-ray diffraction intensities of the 111 Bragg points [28]. The relationship between M and D w i has been described as [29]…”
Section: B Debye Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…The phase transition from the solid-solution (-phase) to hydride (-phase) of Pd was reported using pressure -composition-temperature (PCT) measurement even in NPs in the diameter range of 2 to 3 nm. Kobayashi et al reported that absorbed hydrogen atoms are strongly trapped and stabilized in the lattice of Pd NPs, compared to bulk Pd, resulting the incomplete recovery in the reversing absorption and desorption process of the PCT measurement [1]. Hydrogen-absorption properties of metal NPs are strongly correlated with the atomic scale structure and the electronic states.…”
Section: -Oa-02mentioning
confidence: 99%
“…PbTiO3 perovskite was carried out in the wide temperature range 298-928 K[1]. A transition from a tetragonal (P4mm) to a cubic (Pm3__ _ m) phase has been revealed near 753 K. In the acentric P4mm symmetry group, the difference in relative displacement between Pb and O along the c-axis is much larger than that between Ti and O.…”
mentioning
confidence: 99%